Social Innovation in the Provision of Services in Long-term Care - Széman, Zsuzsa; Tróbert, Anett Mária (European Journal of Mental Health, 2017)
The present study focuses on the potential of extension of social innovation in social services in long-term care. The aim of the paper is to analyse barriers and drivers according to different care regimes: 1. standard care-mix regimes; 2. universal-Nordic; 3. family-based; 4. Central and Eastern European. Applying different qualitative methods (mapping of initiatives, 62 good examples of which 18 were in-depth, expert interviews, focus groups), the paper is going to explore similarities and differences between care regimes with a special focus on Central and Eastern Europe to see whether the Central and Eastern European care regime can be considered as a special one or not. It becomes clear from the analysis that there are similarities and differences between the individual care regimes and it is of fundamental importance that these as well as the good practices should be widely known and transferred or adapted to the given care structure. This requires continuous mapping and research.